PANGGILAN KRISTIANI, GEREJA, FILSAFAT DAN PANCASILA - Suseno, Franz Magnis (UNIKA Santo Thomas, 2020)
In this paper the author reflects on the vocation of Catholic places for the study of philosophy and theology. Believing the gospel, Christians are called to give witness to its redeeming power. But almost from the very beginning Christians felt the need to understand what they believe. From this need rose theology and philosophy. Protestantism, enlightenment and secularism posed new challenges. Aware of them the Catholic Church, since the Council of Trent, obliges her priests to study philosophy and theology. The author then suggests that not only future priests, but also religious sisters, brothers and lay people should get a solid philosophical and theological formation. Our teaching of philosophy should be open also to non-Catholics and non-Christians. Our philosophical and theological institutions must not be inward looking, but enter into the intellectual discourse of the whole society. Turning to Indonesia the author shows that state philosophy Pancasila poses an intellectual challenge for Catholic philosophers they should take up. As a closing note the author points to new challenges the Catholic Church faces after the Second Vatican Council. Indonesian Catholic philosophers and theologians should take an active part in facing them.